Socio-technical aspects of concurrent engineering in construction - a German perspective - Hachmann, Patrik (Department of Construction Economics and Management, 2024)
Collaborative working in construction is becoming an increasingly important management strategy as many design activities and tasks usually require the involvement of project participants from multiple disciplines and functions based in different geographical locations. Recent years have seen the emergence and development of diverse IT- and Web-based tools, standards, methods and techniques for the concurrent exchange and sharing of information between software applications and project participants. However, the implementation of collaborative tools and management approaches such as web-based project management to facilitate concurrent engineering (CE) in the AEC sector faces barriers deriving from technical and sector specific issues, but also from socio-technical and organisational factors. As socio-technical issues have been neglected in research, this study investigates these socio-technical barriers with regard to performance improvements of CE teams in the construction industry. It is based on three German construction projects and uses a qualitative case study methodology with a broadly phenomenological paradigm supported by a quantitative questionnaire survey. The research identifies a number of issues such as the introduction of new communication patterns, the dependence on web-based collaboration tools and technologies, the necessary redesign of the processes, or new job characteristics in collaborative environments and shows how they impact on the interaction of CE teams in the AEC industries. The research results show that despite its technically advanced infrastructure the management approaches to organise and regulate the socio-technical infrastructure in conventional projects are obviously not yet suited to CE in construction environments. The research recommends that new formal methodologies and management strategies have to be established in order to overcome barriers that negatively influence performance improvements in collaborative, multidisciplinary, and physically dispersed settings.